Do We Know What We Enjoy? Accuracy of Forecasted Eating Happiness - Villinger, Karoline; Wahl, Deborah R.; König, Laura M.; Ziesemer, Katrin; Butscher, Simon; Müller, Jens; Reiterer, Harald; Schupp, Harald T.; Renner, Britta (Frontiers in Psychology, 2020)
Forecasting how we will react in the future is important in every area of our lives. However, people often demonstrate an ‘impact bias’ which leads them to inaccurately forecast their affective reactions to distinct and outstanding future events. The present study examined forecasting accuracy for a day-to-day repetitive experience for which people have a wealth of past experiences (eating happiness), along with dispositional expectations towards eating (‘foodiness’). Seventy-three participants (67.12% women, Mage = 41.85 years) used a smartphone-based Ecological Momentary Assessment to assess their food intake and eating happiness over 14 days. Eating happiness experienced in-the-moment showed considerable inter-and intra-individual variation, ICC = .47. Comparing forecasted and in-the-moment eating happiness revealed a significant discrepancy whose magnitude was affected by dispositional expectations and the variability of the experience. The results demonstrate that biased forecasts are a general phenomenon prevalent both in outstanding and well-known experiences, while also emphasizing the importance of inter-individual differences for a detailed understanding of affective forecasting.